Fear as a mythological motif in epic works (based on the work of O. Bukeev «Scream») (Eurasian Journal of Philology Science and Education, 2016)
The article based on the novel «Scream» of Kazakh writer O.Bokeev, analyzes the problem of the fear as one of the major mythological motifs. The fear is associated with exploration of the unknown world not only in mythological, also in artistic time. In the novel «Scream» the unknown world is – Kazakh severe nature, mountains, steppe, etc. O.Bokeev was one of representatives of creative generation of the last Soviet literature, considering to find creative advantage the person. And it as many colleagues on a feather, in possible degree I tried to avoid false romanticism, pathos of artificial heroics, creation of a positive image bearing the ideological contents and so forth. One of the main properties characterizing its images, that they represent ordinary people is.
Keywords: mythological motif; fear; shame; nature; image.